EFL Students’ Anxiety Experience in Speaking English - Poppi Aprilianti Sugito Putri; Maisa; Diana Rahmawati Rozak (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2022)
The purpose of this study is to analyze the factors that cause students' speaking anxiety and how to overcome students' speaking anxiety. This research is qualitative research with data collection techniques using observation, questionnaires and interviews. The participants of this study were 11th grade high school students. The results revealed several factors that cause anxiety in students such as: (1) the students felt embarrassed by being marked with anxiety when talking to other people; (2) the students felt anxious when they were about to face a foreign language speaking exam; and (3) finally the students felt anxious about the opinions or judgments of others when speaking in English in front of the class. It was also found several ways that the students used to reduce students' speaking anxiety such as: (1) the students must prepare in advance such as practicing speaking; (2) the students took a breath to feel relaxed; (3) the students thought positively and looked for peers to share things with each other in order to reduce anxiety.